IMPLEMENTASI TUGAS POKOK GURU PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM 2013 - Asmara Yumarni; liza Aprillia (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
The purpose of this study was to determine the implementation of the main tasks of Islamic Religious Education teachers in the 2013 curriculum of study in class X SMA Negeri Purwodadi, Musi Rawas Regency. This research is using qualitative methods with descriptive research type. Data collection techniques using observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, and data display. The results of the study Implementation of the main tasks of Islamic religious education teachers in the 2013 curriculum, the duties of a teacher in the 2013 curriculum can be seen from the implementation of communication, natural resources, disposition, the teacher's bureaucratic structure has used the 2013 curriculum even though there has been a one year gap because of the lack of facilities. The facilities and infrastructure to support the 2013 curriculum. In law number 14 of 2005 concerning teachers and lecturers chapter 1 article 1 teacher's must be able to educate, teach, train, guide, direct learning, and evaluate. The 2013 curriculum is more pressing in knowledge, skills, and attitudes. Because there are still many students at Purwodadi State High School who have not obeyed the regulations, the difficulty of teachers in carrying out their duties is due to the new curriculum. Therefore, further emphasize the main task of the teacher so that the learning process runs effectively and efficiently.